Aspirin affects early phases of metastasis through the inhibition of COX-1-thromboxane A2 axis - Lucotti, S (2016)
Metastasis is the major cause of cancer related mortality, due to a poor understanding of the metastatic process and a subsequent lack of effective anti-metastatic therapies. Evidence from experimental studies and clinical trials has shown that aspirin reduces the incidence of distant metastases. It is well established that aspirin inhibits cyclooxygenase (COX)-1 and COX-2, triggering anti-thrombotic and anti-inflammatory effects, respectively. However, the mechanisms underlying the anti-metastatic effect of aspirin are still largely unknown. By using an experimental model of pulmonary metastasis, we have found that the anti-metastatic effect of aspirin is associated with the inhibition of COX-1. In support of this, metastasis establishment was impaired in COX-1 deficient mice, suggesting a pivotal role of this isoform in the metastatic process. Looking in more detail into the metastatic cascade, we found that COX-1 contributes to the intravascular phase of metastasis and promotes the early persistence of tumour cells in the lung vasculature. In particular, COX-1 inhibition decreased the interaction of platelets with tumour cells and was associated with the reduction of endothelial activation, of tumour cell adhesion to the endothelium, of recruitment of metastasis-promoting monocytes/macrophages and of transendothelial migration. We have identified platelet-derived thromboxane A2 (TXA2) as the main product of COX-1 responsible for its permissive effect on metastasis. Indeed, TXA2 delivered to mice in combination with aspirin was able to abrogate the anti-metastatic effect of aspirin. Taken together, our data suggest that the inhibition of COX-1:TXA2 axis by aspirin is sufficient to exert an anti-metastatic effect. In particular, the inhibition of platelet-derived TXA2 seems to affect multiple early steps of the haematogenous transit of tumour cells. In this perspective, TXA2 might represent a more selective therapeutic target for the prevention of metastasis.